2020
DOI: 10.1172/jci131859
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glutamine metabolism enhances tumor-specific immunity by modulating suppressive myeloid cells

Abstract: Conflict of interest: JDP, BSS, RR, and PM are scientific founders of Dracen Pharmaceuticals and possess equity. Technology arising in part from the studies described herein were patented by Johns Hopkins University and subsequently licensed to Dracen Pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
245
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(251 citation statements)
references
References 63 publications
5
245
1
Order By: Relevance
“…In the context of metabolism, this complex interplay between cancer cells and immune cells present in the micro-environment gives a new dimension to the use of drugs that target metabolic processes (O'Sullivan et al, 2019;Patel et al, 2019). For instance, inhibiting glutamine metabolism has been shown to inhibit tumor growth and increase the sensitivity of triple-negative breast cancers to immune checkpoint blockade (Oh et al, 2020), and reducing oxidative stress has been shown to prevent the generation of tumor-associated macrophages (Zhang et al, 2013). Furthermore, modulating metabolism in T-cells from glycolytic towards an OXPHOS-weighted profile has been shown to improve CAR T cell immunotherapy (Fraietta et al, 2018;O'Sullivan and Pearce, 2015;Sukumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of metabolism, this complex interplay between cancer cells and immune cells present in the micro-environment gives a new dimension to the use of drugs that target metabolic processes (O'Sullivan et al, 2019;Patel et al, 2019). For instance, inhibiting glutamine metabolism has been shown to inhibit tumor growth and increase the sensitivity of triple-negative breast cancers to immune checkpoint blockade (Oh et al, 2020), and reducing oxidative stress has been shown to prevent the generation of tumor-associated macrophages (Zhang et al, 2013). Furthermore, modulating metabolism in T-cells from glycolytic towards an OXPHOS-weighted profile has been shown to improve CAR T cell immunotherapy (Fraietta et al, 2018;O'Sullivan and Pearce, 2015;Sukumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to glycolysis, some cells utilize glutamine to maintain mitochondrial metabolites for ATP and macromolecule synthesis 25,26 . Recent work has shown that inhibiting TME glutamine metabolism can impair cancer cell growth while increasing anti-tumor immunity 12,13,15 . In contrast to our finding that glucose uptake is highest in tumor-infiltrating immune cells, we hypothesized that glutamine uptake might more preferentially support cancer cell metabolism.…”
Section: Glutamine Partitions Into Cancer Cellsmentioning
confidence: 99%
“…These data also support the notion that targeting glutamine metabolism presents a specific strategy to hamper cancer cell growth. Intriguingly, this approach also increases glucose consumption by all TME resident cell types and may alter antitumor immunity 12,13,15 . Given the current interest in glutamine-targeting therapeutics, our findings contribute a model of nutrient partitioning that supports their further development.…”
Section: Selective Nutrient Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, suppresses the development of metastasis and further enhances anti-tumor immunity. Additionally, targeting glutamine metabolism makes it easier for checkpoint blocking drug-resistant tumors to receive immunotherapy [ 62 ]. This proves once again that MDSCs and cancer cells have similar metabolic characteristics to a certain extent, and there is a close interaction between the unique metabolism of tumor and the metabolism of inhibitory immune cells.…”
Section: Metabolism Of Mdscsmentioning
confidence: 99%